Tuning rules for energy-based control methods for mechanical systems - Chan Zheng, Carmen 1989- (Groningen, 2023)
Modern applications demand faster, more sophisticated, more precise, and more powerful robotic systems that can handle harsh environments. Simultaneously, this trend also creates new challenges for modeling and control design as the nonlinear phenomena are no longer negligible. Despite the popularity of linear control techniques in the industry -due to their availability- they are not suitable to deal with the demands as nonlinear dynamics are becoming richer. In fact, disregarding these behaviors during the modeling and control design stages may lead to poor performance or instability. For example, the effect of "hard linearities" -such as Coulomb friction, dead-zones, saturation, asymmetry of the motors, backslash, or hysteresis- cannot be analyzed with linear techniques, and these phenomena may lead to steady-state errors. Regardless of the clear advantages of the nonlinear control schemes - e.g., stability guarantees are inherent in these methodologies - in comparison with their linear counterpart, there is still an evident gap between practitioners and theorists. The implementation of the nonlinear schemes is hampered in practice due to the lack of tuning guidelines in the literature as the vast majority of the methodologies are devoted to designing controllers to achieve the performance in terms of stability, disregarding other performance indices. Nonetheless, in several applications, it is crucial to prescribe per- formance to solve a task at hand, e.g., high-precision applications such as those found in medical, aerospace, and other industries. Hence, this thesis provides a comprehensive set of tuning rules for a class of nonlinear control schemes, namely, passivity-based control (PBC) approaches. These schemes aim to render the closed loop stable via two steps: i) the energy shaping (or power shaping) process and ii) the damping injection step. For the former step, the energy shaping (or power shaping) process assigns the desired...
Moderne toepassingen vragen snellere, meer verfijnde, preciezere en sterkere robotsystemen die beter bestand zijn tegen zware omstandigheden. Tegelijkertijd creëert deze trend nieuwe uitdagingen voor het modelleren en regelen nu de niet-lineaire verschijn- selen niet langer verwaarloosbaar zijn. Ondanks de populariteit van de lineaire regeltechnieken in de industrie - wegens hun beschikbaarheid - , voldoen deze niet aan de gestelde eisen nu de niet-lineaire dynamica steeds complexer wordt. Sterker nog, het negeren van deze dynamica tijdens het modelleren en regelaarontwerp kan leiden tot een slechte werking of instabiliteit. Bijvoorbeeld, het effect van "hard non-linearities" - zoals de Coulomb frictie, dode-zones, saturatie, asymmetrie van de motoren of backlash/hysterese - kan niet worden geanalyseerd met lineaire technieken, en deze verschijnselen kunnen tot fouten in de evenwichtstoestand leiden. Ondanks de duidelijke voordelen van niet-lineaire regelsystemen - de garantie op stabiliteit is inherent aan deze methodologie - in vergelijking met hun lineaire tegenhanger, bestaat er nog altijd een duidelijk kloof tussen de praktijk en de theorie. De implementatie van niet-lineaire schema's wordt in de praktijk belemmerd door het ge- brek aan tuningregels in de literatuur, omdat de meeste methodologiën zijn toegespitst op het ontwerpen van regelaars die de systemen stabiliseren, daarbij andere kwaliteitskenmerken negerend. Desalnietemin is het cruciaal om bij verschillende toepassingen een specifiek gedrag voor te schrijven om een taak te volbrengen, bv. bij hoge precisie toepassingen zoals die in medische-, lucht- en ruimtevaart- en andere industrieën. Dit proefschrift behandelt tuningregels voor niet-lineaire regelaarontwerp gebaseerd op het concept van passiviteit (PBC). Deze regelaarontwerpen hebben als doel om de ge- sloten kring passief te maken via twee stappen: i) het proces van het aan passen van de interne energie...
Las aplicaciones modernas exigen sistemas robóticos más rápidos, más sofisticados, más precisos y más potentes que puedan funcionar en entornos hostiles. Simultáneamente, esta tendencia también crea nuevos desafíos para el modelado y el control, dado que los fenómenos no lineales son cada vez más difíciles de despreciar. A pesar de la popularidad de las técnicas lineales en la industria -debido a su alta disponibilidad- éstas ya no son adecuadas para hacer frente a las demandas a medida que la dinámica de los fenómenos no lineales se está volviendo más compleja. De hecho, ignorar estos comportamientos durante las etapas de modelado y diseño del controlador puede conducir a un rendimiento deficiente o incluso inestabilidad del lazo cerrado. Por ejemplo, el efecto de las linealidades complejas- como la fricción de Coulomb, zonas muertas, saturación de los actuadores, asimetría de los motores, backslash o histéresis- no se puede analizar con técnicas lineales. Adicionalmente, estos fenómenos pueden resultar en errores de estado estacionario. Independientemente de las claras ventajas de los esquemas de control no lineal- por ejemplo, las garantías de estabilidad son inherentes a estas metodologías- en comparación con su contraparte lineal, hay una brecha evidente entre los practicantes y los teóricos. La implementación de los esquemas no lineales se ve obstaculizada en la práctica debido a la falta de pautas de ajuste en la literatura. La gran mayoría de las metodologías se dedican a diseñar controladores para lograr el rendimiento en términos de estabilidad, sin tener en cuenta otros índices de rendimiento. No obstante, en varias aplicaciones, es crucial prescribir el rendimiento para resolver una tarea específica. Por ejemplo: aplicaciones de alta precisión, como las que se encuentran en la industria médica, aeroespacial. Esta tesis proporciona un conjunto de reglas de ajuste para una clase...
Tesis (doctorado)--University of Groningen, 2023
Se considera un trabajo Final de Graduación del Sistema de Estudios de Posgrado, según oficio no. OAICE-1139-2023
Keywords: SISTEMAS DE CONTROL; CONTROLADORES PID; SISTEMAS DE CONTROL DE AUTOMATAS; MOVIMIENTOS MECANICOS